Ateliê de memórias – narrativas autobiográficas de ingressantes no ensino superior - Vaiano, Camila Lopes (2019)
This master’s thesis intends to understand, through the college students' narratives, what hinders and facilitates the academic insertion of these students. This study was anchored in an academic setting project called Ateliê de Memórias. This Project was developed in a private college, in São Paulo (SP), which used as an especific teaching methodology – Comprehensive Teaching and Integrated Curriculum. The idea was that students could narrate their life stories in small work groups and the difficulties faced in their educational processes, because they were too common in the entrance in a college in Brazil. So, students was invited to turn these (auto) biographies into children's books. Spicific and themed academic works which investigate the process of (self) formation, narrative research and academic belonging were brought to a dialogue and research rationale. This thesis presents 61 students, who entered in three tecnological courses – Graphic Design, Audiovisual Production and Advertising Production. The research corpus consisted of the researcher's journal and nine (auto) biographical books produced by the students at Ateliê de Memórias project. In the present research we used the qualitative approach, as a proposal to dialogue with social subjects which have experiences about insertion in college education. More specifically, it relied on research based on the (auto) biographical narratives of these students. From the analysis of their narratives it was possible to identify values, beliefs and representations (collective and individual) that they built in their lives, before their entry into college education as a means to face difficult situations. Understanding what makes it difficult and what facilitates the academic insertion of students entering the college level of this work, admits the premise that, based on teaching for understanding, the insertion in the activities of the college degree is related to the degree of belonging of the students. In Ateliê de Memórias, the collective narrative work of each participant, the pooling of questions, restlessnesses and concerns, allowed students to emerge from isolation, their own problems, and to reflect on the possibility of using resources that were previously unusual, they came from specific ways from their own experiences, to solve their problems and adapt to their realities.